SADOU : REPRESENTASI KERAMAHTAMAHAN ASIA TIMUR - Sri Wahyu Istana Trahutami (KIRYOKU, 2018)
(Title: Sadou: Representation Of East Asia Hospitality) Sadou is a Japanese traditional etiquette of preparing and drinking tea and was originally developed from China. Sadou brought to Japan by  Buddhist monk from China. Although the main purpose is to enjoy tea however the manner, performance, tea equipment, tea room, and the decoration of the tea room are also important and performed as part of the composite arts. Ichi go ichi e is a concept connected to the way of tea (sadou) is expresses the ideal of the way of tea. The phrase means ‘one time one meeting’ or ‘one encounter one opportunity’. In sadou we should respect the host and the others in the tea room and honor the moment as if it were a once in a lifetime gathering. That is we should cherish every meeting for it will never happen again. ichi go ichi e is the reminder that each tea ceremony is unique even though the elements are familiar.